2013
DOI: 10.1038/nrc3603
|View full text |Cite
|
Sign up to set email alerts
|

The roles of TGFβ in the tumour microenvironment

Abstract: The influence of the microenvironment on tumour progression is becoming clearer. In this Review we address the role of an essential signalling pathway, that of transforming growth factor-β, in the regulation of components of the tumour microenvironment and how this contributes to tumour progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
732
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 801 publications
(750 citation statements)
references
References 150 publications
13
732
1
4
Order By: Relevance
“…10 TGF-b isoforms signal through canonical signaling pathways that include activation of SMAD proteins or through noncanonical signaling pathways that include phosphatidylinositol 3-kinase, RhoA, or TAK1 pathways. 10,11 Procancer effects may be driven by either canonical or noncanonical activity, with noncanonical activity shown to promote cancer cell invasion through induction of epithelial-mesenchymal transition (EMT), modulation of miRNA levels, and stimulation of mTOR activity. 12e15 Recent work has also suggested a role for TGF-b in regulating cancer progression through effects on the tumor microenvironment, including immune modulation and effects on cancer-associated fibroblasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 TGF-b isoforms signal through canonical signaling pathways that include activation of SMAD proteins or through noncanonical signaling pathways that include phosphatidylinositol 3-kinase, RhoA, or TAK1 pathways. 10,11 Procancer effects may be driven by either canonical or noncanonical activity, with noncanonical activity shown to promote cancer cell invasion through induction of epithelial-mesenchymal transition (EMT), modulation of miRNA levels, and stimulation of mTOR activity. 12e15 Recent work has also suggested a role for TGF-b in regulating cancer progression through effects on the tumor microenvironment, including immune modulation and effects on cancer-associated fibroblasts.…”
mentioning
confidence: 99%
“…12e15 Recent work has also suggested a role for TGF-b in regulating cancer progression through effects on the tumor microenvironment, including immune modulation and effects on cancer-associated fibroblasts. 10,11 The role of TGF-b in bladder cancer has been studied in significantly less detail. It has been shown that several singlenucleotide polymorphisms in genes encoding TGF-b1 and the TGF-b receptor I (TGFbRI) appear to be involved in bladder cancer risk and prognosis.…”
mentioning
confidence: 99%
“…67 Many tissue-specific knockout mouse models have also been generated that clearly demonstrate the tumor suppressor activity of TGFb in a variety of organs, including the breast. 64 Some of these models have made clear that the more sensitive cell type to the tumor-derived TGFb are the resident fibroblasts of the tumor stroma or immune cells, such as T lymphocytes that contribute to enhanced tumor growth and cancer progression when TGFb receptor or Smad signaling is lost in these cells. 68 The other face of TGFb in tumor progression is a protumorigenic that seems to be more universal and usually is linked to every tumor type studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…7 b) However, the pro-EMT action of TGFb represents a pro-tumorigenic and pro-metastatic aspect of the biology of this growth factor in the context of cancer. 64 In the sequence of multi-stage events of cancer progression, the pro-tumorigenic TGFb actions are usually thought to follow the tumor suppressive effects that TGFb exhibits as a factor that maintains epithelial tissue homeostasis. 64 In other words, the pro-tumorigenic, pro-EMT effects of TGFb, at the cellular level correlate to one of the hallmarks of the tumor suppressive effects TGFb has.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation